A QbD Approach to Continuous Tablet Manufacture. (2015) - Freeman, Tim; Birkmire, Andrew; Armstrong, Brian
Abstract: The pharmaceutical industry is looking to continuous processing to enhance production efficiency and product quality, in line with guidance from regulatory agencies. It is therefore necessary to define and link material quality parameters, at all stages during processing, to those of the final product. This study investigates the performance of a continuous granulation system and shows how key properties of the granules, which are a direct function of the operational conditions of the granulator, can be identified, measured and linked directly to the Critical Quality Attributes of the tablets manufactured from these granules.